2007
DOI: 10.2471/blt.06.033076
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment roll-out in a resource-constrained setting: capitalizing on nursing resources in Botswana

Abstract: Problem As programmes to deliver antiretroviral therapy (ART) are implemented in resource-constrained settings, the problem becomes not how these programmes are going to be financed but who will be responsible for delivering and sustaining them. Approach Physician-led models of HIV treatment and care that have evolved in industrialized countries are not replicable in settings with a high prevalence of HIV infection and limited access to medical staff. Therefore, models of care need to make better use of availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 23 publications
0
42
0
3
Order By: Relevance
“…Furthermore, although medical doctors are commonly perceived as the guardians of technical quality, a clinical approach isolated from the community is not ideal. The involvement of other cadres 11 and communities in support and care [12][13][14] brings benefi ts by increasing coverage and improving overall outcomes. 11,13 Patients, health staff , and policy makers need to be involved in setting measurable targets and indicators for what they deem to be an acceptable level of quality of care.…”
mentioning
confidence: 99%
“…Furthermore, although medical doctors are commonly perceived as the guardians of technical quality, a clinical approach isolated from the community is not ideal. The involvement of other cadres 11 and communities in support and care [12][13][14] brings benefi ts by increasing coverage and improving overall outcomes. 11,13 Patients, health staff , and policy makers need to be involved in setting measurable targets and indicators for what they deem to be an acceptable level of quality of care.…”
mentioning
confidence: 99%
“…Conditions for scale up described in the literature include establishing clear policy and implementation networks between state and non-state sectors [3,34], consideration of task shifting in order to meet the human-resource demands of providing the desired service [35,36], appropriate contextual application of existing and emerging evidence [3,37], and advocacy for the outcome amongst healthcare professionals [38]. Once there is robust evidence to support the use of a particular tool or package in an implementation programme, the feasibility of scale up should be ascertained [3].…”
Section: Conditions For Scaling Up Emonc Programmesmentioning
confidence: 99%
“…Experiences in Zambia and Botswana illustrated that shifting the task of ART initiation to nurses has the potential to improve ART coverage (5,6), and the CD4 Nurse Intervention in…”
Section: Professional Competencementioning
confidence: 99%
“…However, there was no empirical evidence that demonstrated that the nurses could perform as safe, accountable and acceptable practitioners. Therefore, controlled trials and formative research are needed to provide empirical data on the benefits and risks of this strategy compared to traditional models (6). Task shifting might also have consequences such as imposing new responsibilities on some staff and removing tasks from others (2).…”
Section: Ethiop J Health Dev 2009;23(3)mentioning
confidence: 99%